Increased mid‐abdominal circumference is a predictor for surgical wound complications in kidney transplant recipients: A prospective cohort study. Issue 5 (4th April 2017) - Taha, Mohamed; Davis, Niall F.; Power, Richard; Mohan, Ponusamy; Forde, James; Smyth, Gordon; Little, Dilly M.
Abstract: Kidney transplant recipients are at an increased risk of developing surgical site wound complications due to their immunosuppressed status. We aimed to determine whether increased mid‐abdominal circumference (MAC) is predictive for wound complications in transplant recipients. A prospective study was performed on all kidney transplant recipients from October 2014 to October 2015. "Controls" consisted of kidney transplant recipients without a surgical site wound complication and "cases" consisted of recipients that developed a wound complication. In total, 144 patients underwent kidney transplantation and 107 patients met inclusion criteria. Postoperative wound complications were documented in 28 (26%) patients. Patients that developed a wound complication had a significantly greater MAC, body mass index (BMI), and body weight upon renal transplantation ( P <.001, P =.011, and P =.011, respectively). On single and multiple logistic regression analyses, MAC was a significant predictor for developing a surgical wound complication ( P =.02). Delayed graft function and a history of preformed anti‐HLA antibodies were also predictive for surgical wound complications ( P =.003 and P =.014, respectively). Increased MAC is a significant predictor for surgical wound complications in kidney transplant recipients. Integrating clinical methods for measuring visceral adiposity may be useful for stratifying kidney transplant recipients with an increased risk of a surgical wound complication.